Penerapan Metode Weighted Product (WP) untuk Menentukan Penerimaan BLT di Desa Rawasari - Joko Kuswanto; Ardha Febriyanti Wulandari; Indri Yani; Sheyla Rizky Novanto Samudra; Jum Dapiokta (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
One of the government's programs to overcome poverty problems is the distribution of Bantuan Langsung Tunai (BLT). Bantuan Langsung Tunai (BLT) is a form of assistance from the government as a form of compensation from the increase in the price of Fuel Oil (BBM). In providing BLT to rural communities in Indonesia, the government has certainly set several criteria in determining who is entitled to receive the assistance.  Therefore, a decision support system is needed that can help provide recommendations for choices in effective and efficient decision making.  The decision support system to be built applies the Weighted Product (WP) method in accordance with administrative assessment criteria and BLT information, so that information can be conveyed quickly and administrative management is more transparent and effective. After searching for vectors to get a BLT, the largest vector value of 0.06006 obtained by Rizki thus Rizki's feasible alternatives became a priority to get BLT-Dana Desa and were recommended in receiving assistance.